2007
DOI: 10.1001/archpsyc.64.8.932
|View full text |Cite
|
Sign up to set email alerts
|

Depressed Dopamine Activity in Caudate and Preliminary Evidence of Limbic Involvement in Adults With Attention-Deficit/Hyperactivity Disorder

Abstract: Context: Attention-deficit/hyperactivity disorder (ADHD) is the most prevalent psychiatric disorder of childhood. There is considerable evidence that brain dopamine is involved in ADHD, but it is unclear whether dopamine activity is enhanced or depressed.Objective: To test the hypotheses that striatal dopamine activity is depressed in ADHD and that this contributes to symptoms of inattention.Design: Clinical (ADHD adult) and comparison (healthy control) subjects were scanned with positron emission tomography a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

18
181
3
5

Year Published

2007
2007
2014
2014

Publication Types

Select...
7
2

Relationship

2
7

Authors

Journals

citations
Cited by 282 publications
(212 citation statements)
references
References 58 publications
18
181
3
5
Order By: Relevance
“…41 It is not surprising that we found a reduced volume of a portion the caudate, given that studies using diverse functional imaging techniques (e.g., positron emission tomography) have shown a malfunction in the striatum of adults with ADHD. [42][43][44] Considering our findings and the fact that few studies involving adult ADHD patients have been published, there is a need for additional research into the volume of the caudate nucleus in adults with ADHD.…”
Section: Discussionmentioning
confidence: 92%
“…41 It is not surprising that we found a reduced volume of a portion the caudate, given that studies using diverse functional imaging techniques (e.g., positron emission tomography) have shown a malfunction in the striatum of adults with ADHD. [42][43][44] Considering our findings and the fact that few studies involving adult ADHD patients have been published, there is a need for additional research into the volume of the caudate nucleus in adults with ADHD.…”
Section: Discussionmentioning
confidence: 92%
“…It has been found that iron is closely related to dopamine metabolism being a coenzyme of tyrosine hydroxylase, and that D2 and D4 receptor and dopamine transporter densities decrease with decreased brain iron levels [8][9][10]. It can be speculated that iron deficiency may cause further alterations in brain dopaminergic system, which seems to be already impaired in ADHD subjects [20]. It has been proposed that there might be multiple developmental pathways for ADHD that includes different neuropsychological subtypes [21].…”
Section: Discussionmentioning
confidence: 99%
“…A recent positron emission tomography report of 13 healthy adults [11] found increased density of cortical dopamine D1 receptor binding in the PFC and parietal cortex associated with WM training. Thus, training may improve behavioral and cognitive impairments of ADHD related to disturbances of the dopamine system [11,45]. These neuroimaging findings suggest that WM training may have the potential for improved generalization by targeting core weaknesses involved in executive functioning in ADHD populations.…”
Section: Introductionmentioning
confidence: 91%
“…A functional magnetic resonance study of training in ADHD using a broad package of exercises [44], focusing on response inhibition and selective attention rather than WM, found increased frontal, middle temporal, and cerebellar activity after training. Theoretically, improvement in dopamine functioning, which is altered in ADHD and is targeted by the most efficacious ADHD pharmacologic treatments [45], would also enhance the generalization of training effects. A recent positron emission tomography report of 13 healthy adults [11] found increased density of cortical dopamine D1 receptor binding in the PFC and parietal cortex associated with WM training.…”
Section: Introductionmentioning
confidence: 99%